Chronic pulmonary aspiration in children - Anna Campanario-Cañizo; José A. Gil-Sánchez; José A. Peña-Zarza; Joan Figuerola-Mulet (Barcelona Respiratory Network Reviews)
Chronic pulmonary aspiration is a common issue in the pediatric population, particularly in patients with neurological conditions, anatomical malformations, and infants with a history of prematurity. Its clinical manifestations are highly varied, with chronic cough, wheezing, recurrent bronchitis, and pneumonia being the most prominent. In many cases, aspiration may be silent, going unnoticed until it results in severe pulmonary damage. Aspiration due to swallowing dysfunction may occur either basally with the aspiration of saliva or during feeding. To diagnose this condition, we have diagnostic tools such as videofluoroscopy and fiber-optic swallowing endoscopy. Respiratory manifestations of gastro-esophageal reflux may occur in the absence of digestive symptoms. There is no gold standard for its diagnosis, making it essential to conduct a thorough assessment and employ appropriate diagnostic tools. Tracheo-oesophageal fistulas are often associated with respiratory manifestations, even when they have been surgically repaired.